Individualism: the end of social cohesion? The effects of inequality and group identity on cooperation - Senn, Sebastian; Mutzner, Nico; Oberhauser, Vincent; Rauhut, Heiko (Frontiers in Behavioral Economics, 2025)
IntroductionGlobal challenges like pandemics and climate change are fundamentally cooperation problems, where individual interests often conflict with the collective good. Rising economic inequality and individualism are believed to erode social cohesion and cooperation, exacerbating these tensions. Public goods games (PGGs) are widely used to study cooperation in scenarios of unequal resource distribution, but findings on the effects of inequality remain inconsistent, partly due to varied applications of heterogeneity across studies.MethodsThis study introduces a novel research design that directly compares collectivistic and individualistic groups to examine the combined effects of individualism and inequality on cooperation. Groups were exposed to different resource distribution conditions, including both equal and unequal distributions, and their cooperation rates were measured.ResultsThe findings reveal no significant differences in cooperation rates between collectivistic and individualistic groups. However, groups with higher inequality exhibited significantly higher cooperation rates than those with equal resource distributions. Notably, heterogeneous groups showed considerable variation in their success at establishing cooperation. Further analysis indicates that the willingness to reduce initial inequality served as a strong signal, enhancing group identity and fostering cooperation.DiscussionThe results suggest that in contexts where group identity is strong, inequality can act as a coordination mechanism, enabling groups to distribute the burden of collective costs more effectively and enhancing overall cooperation. These findings challenge the assumption that inequality inherently undermines cooperation and highlight the potential for strategically leveraging inequality in contexts characterized by collectivistic norms.